The Saccharomyces cerevisiae RAD18 gene encodes a protein that contains potential zinc finger domains for nucleic acid binding and a putative nucleotide binding sequence. - Jones, J S (1988)
The RAD18 gene of Saccharomyces cerevisiae is required for postreplication repair of UV damaged DNA. We have isolated the RAD18 gene, determined its nucleotide sequence and examined if deletion mutations of this gene show different or more pronounced phenotypic effects than the previously described point mutations. The RAD18 gene open reading frame encodes a protein of 487 amino acids, with a calculated molecular weight of 55,512. The RAD18 protein contains three potential zinc finger domains for nucleic acid binding, and a putative nucleotide binding sequence that is present in many proteins that bind and hydrolyze ATP. The DNA binding and nucleotide binding activities could enable the RAD18 protein to bind damaged sites in the template DNA with high affinity. Alternatively, or in addition, RAD18 protein may be a transcriptional regulator. The rad18 deletion mutation resembles the previously described point mutations in its effects on viability, DNA repair, UV mutagenesis, and sporulation.